Explaining the Unexplained: Situational Differences in Fundamental Attribution Error - Dong, Peilin (International Journal of Social Science Research, 2024)
Fundamental Attribution Error (FAE) has been one of the most investigated aspects of human bias. This research seeks to distinguish between the two most common explanations: the cognitive stage theory and the motivational explanation. Participants were given three scenarios in which participants were asked to explain a described event where something happens to another group of people. Each scenario differed from the others in terms of proximity to and effect on the observer, but all three were described without explanation. Mixed-method analysis of the responses of 81 participants contributed to a better understanding of FAE by supporting a hierarchical predictive model based on motivational explanations as the strongest model for FAE. Furthermore, the findings support an interaction between self-serving bias and FAE, but do not support cultural effects on FAE.